الفنادق البيئية كأحد الخيارات لتحقيق التنمية السياحية المستدامة - عباس, زهرة; بن عويدة, نجوى (جامعة الوادي - University of Eloued, 2021)
يعد قطاع السياحة من القطاعات التي تحظى باهتمام كبير وذلك لما تلعبه من دور بارز في دفع عجلة التنمية. إلا أنها قد تساهم في تلويث البيئة والإضرار بها إدا ما تم إدارة هذا النشاط بطريقة غير كفؤة، الأمر الذي يتطلب إدخال معايير جديدة على القطاع السياحي ولتنميته بشكل مستدام وبالأخص القطاع الفندقي. تهدف هذه الدراسة إلى تسليط الضوء من جهة على مفهوم التنمية السياحية المستدامة، ومن جهة أخرى التطرق لمفهوم الفنادق الخضراء كأحد الخيارات الممكنة للمساهمة في تجسيد مفهوم التنمية السياحية المستدامة. وقد توصلت الدراسة إلى عدة نتائج أبرزها أن المساهمة في تحقيق تنمية سياحية مستدامة من خلال إنشاء الفنادق البيئية لا بد أن يستجيب للمتطلبات والمعايير البيئية في جميع مراحل إنشائها إلى غاية نشاطها، وكذا ضرورة احترامها لمبادئ الاستدامة، وللهوية الثقافية والحضارية للمنطقة التي تتواجد بها. The tourism sector is among the sectors that receive great attention due to the prominent role it plays in advancing development. However, it may contribute to polluting and damaging the environment if this activity is managed in an inefficient manner, which requires the introduction of new standards on the tourism sector and its sustainable development, especially the hotel sector. This study aims to shed light on the one hand on the concept of sustainable tourism development, and on the other hand to address the concept of green hotels as one of the possible options to contribute to embodying the concept of sustainable tourism development. The study reached several results, the most prominent of which is that the contribution to achieving sustainable tourism development through the establishment of eco-hotels must meet environmental requirements and standards in all stages of its establishment up to the purpose of its activity, as well as the need to respect the principles of sustainability and the cultural and civilizational identity of the region in which it is located.
Eco-hotels as one of the options to achieve sustainable tourism development
مقال
Keywords: السياحة، الفنادق البيئية، التنمية المستدامة، التنمية السياحية المستدامة.; Tourism, eco-hotels, sustainable development, sustainable tourism development